A tide that cannot be turned. - Stelzer, Irwin (New Statesman, 2001)
Argues that economic self-interest is a better guide to immigration policy in Great Britain than humanitarianism. Statistics of illegal immigrants in the country; Discussion on alien labor and employee mobility; Problems concerning internationally organized people-smuggling rings.